Uma engenharia didática para abordar o conceito de equação diferencial em cursos de Engenharia - Oliveira, Eliane Alves de (2014)
This research had the target to check into teaching strategies that could favour students to learn about Ordinary Differential Equations and their applications inEngineering graduation courses. The study directed to the elaboration of a didactic engineering and was centered in the casting definition of these engineering components, having graphic, algebraic and numerical approaches which involved problem situations by means of the use of computational resources. The Theory of Didactical Situations, by Guy Brosseau and the Didactical Engineering, by Michèle Artigue compose the main theoretical-methodological inputs of the research. Sixteen students of the second year of Environmental Engineering and Production Engineering graduation courses of a higher graduation institution voluntarily joined the experiment. The GeoGebra Software was utilized for that. The data collection was made by using the following instruments: activities guide, initial and final knowledge tests and field diary. The results indicated that the software use favored the activities accomplishment and revealed the importance and productivity of arguments in pairs. The obtained data analysis enabled us to assert that the didactical engineering characteristics developed in this workfavouredthe construction of concepts of Ordinary Differential Equations by the students, attending the research aims